2010
DOI: 10.1021/ac100738b
|View full text |Cite
|
Sign up to set email alerts
|

Shearforce-Based Constant-Distance Scanning Electrochemical Microscopy as Fabrication Tool for Needle-Type Carbon-Fiber Nanoelectrodes

Abstract: Carbon fiber nanoelectrodes with nanometer radii tip curvatures were fabricated using a shearforce-based constant-distance scanning electrochemical microscope and electrochemically induced polymer deposition. A simple DC etching procedure in alkaline solution provided conically sharpened single carbon fibers with well-formed nanocones at their bottom. Coating the stems but not the end of the tips of the tapered structures with anodic electrodeposition paint was the strategy for limiting the bare carbon to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…However, in a previous work [42], we deposited the electrophoretic paint with a different method and it formed a thinner insulating layer closer to the tip apex. Therefore, we believe that these SEM images do not allow visualizing precisely the radius of each electroactive tip because the border of the insulating paint could not be observed by SEM [47,51]. Another interpretation may be that the nanoprobes are not independent and diffusion layer overlapping is encountered along the whole nanoprobe array.…”
Section: Array Of Independent Insulated Nanoprobesmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in a previous work [42], we deposited the electrophoretic paint with a different method and it formed a thinner insulating layer closer to the tip apex. Therefore, we believe that these SEM images do not allow visualizing precisely the radius of each electroactive tip because the border of the insulating paint could not be observed by SEM [47,51]. Another interpretation may be that the nanoprobes are not independent and diffusion layer overlapping is encountered along the whole nanoprobe array.…”
Section: Array Of Independent Insulated Nanoprobesmentioning
confidence: 96%
“…The protocol was then successfully used for the insulation of nanoelectrode arrays prepared from etched optical fiber arrays [43]. More recently, Schulte et al have shown that shearforce detection in SECM could be used as a fabrication tool for needletype carbon-fiber nanoelectrodes [47]. Following this work we would like to evaluate the interest of the shearforce positioning as described in the previous section as a tool for controlled insulation of gold nanotip array with electrophoretic paint.…”
Section: Controlled Insulation Of Nanoprobe Electrode Arraymentioning
confidence: 99%
“…Electrochemically etched carbon nanoelectrodes (7) were employed as non-catalytic conductive supports of single platinum nanoparticles to study their electrocatalytic activities (8). Etched carbon-fiber nanoelectrodes, however, yielded only low SECM feedback responses (9) because of the conical tip geometry (10, 11). Alternatively, disk-shaped carbon nanoelectrodes (12) were developed by pyrolytic deposition of carbon (13).…”
mentioning
confidence: 99%
“…Advantageously, the thin quartz sheath allows for high-resolution transmission electron microscopy (TEM) imaging of the flat and sharp carbon nanotips. The geometry of FIB-milled carbon nanotips is well-controlled not only to quantitatively assess their remarkably high electrochemical reactivity, but also to yield high feedback responses in SECM approach curve measurements in contrast to previously reported carbon nanotips (9, 1417). Good agreement between experimental and simulated approach curves at SiO 2 -coated silicon wafers reliably confirms the well-characterized tip geometry and size, and a lack of a conductive carbon film on the outer tip wall.…”
mentioning
confidence: 99%
“…Here, the SECM probe is excited via lateral vibrations, either mechanically or by attachment to a tuning fork, and certain modes of these lateral oscillations are damped by hydrodynamic forces in proximity to a surface. 71,72 Detection of the shear-force dampening was initially achieved via optical means 97 but alternative detection systems have since been developed, as shown in Fig. 6a).…”
Section: Shear-force Positioningmentioning
confidence: 99%